Measuring digital transformation in higher education institutions – content validity instrument - Castro Benavides, Lina Maria; Tamayo Arias, Johnny Alexander; Burgos, Daniel; Martens, Alke (Applied Computing and Informatics, 2023)
Purpose: This study aims to validate the content of an instrument which identifies the organizational, sociocultural and technological characteristics that foster digital transformation (DT) in higher education institutions (HEIs) through the Delphi method. Design/methodology/approach: The methodology is quantitative, non-experimental, and descriptive in scope. First, expert judges were selected; Second, Aiken's V coefficients were obtained. Nine experts were considered for the validation. Findings: This study’s findings show that the instrument has content validity and there was strong consensus among the judges. The instrument consists of 29 questions; 13 items adjusted and 2 merged. Originality/value: A novel instrument for measuring the DT at HEIs was designed and has content validity, evidenced by Aiken's V coefficients of 0.91 with a 0.05 significance, and consensus among judges evidenced by consensus coefficient of 0.81.
Keywords: Aiken's V; consensus coefficient; content validate; Delphi method; digital transformation; higher education institutions; Scopus